Adult out-of-hospital cardiac arrest in philadelphia from 2008–2012: An epidemiological study. (June 2017) - Gaieski, David F.; Agarwal, Anish K.; Abella, Benjamin S.; Neumar, Robert W.; Mechem, Crawford; Cater, Sarah Wallace; Shofer, Frances S.; Leary, Marion; Pajerowski, William P.; Becker, Lance B.; Carr, Brendan; Merchant, Raina; et al.
Abstract: Background: Wide variation in out-of-hospital cardiac arrest (OHCA) survival has been reported, with low survival in urban settings. We sought to describe the epidemiology of OHCA in Philadelphia, Pennsylvania, the fifth largest U.S. city, and identify potential areas for targeted interventions to improve survival. Methods and results: Retrospective chart review of adult, non-traumatic, OHCA occurring in Philadelphia between 2008 and 2012. We determined incidence and epidemiological factors including: demographics, initial cardiac rhythm, bystander cardiopulmonary resuscitation, automated external defibrillator use, return of spontaneous circulation and 30-day survival. 5198 cases of adult, non-traumatic OHCA were identified. The incidence was 81.5/100, 000. The majority of cases occurred in a residence (76.2%); 30.4% were witnessed events; the initial cardiac rhythm was pulseless ventricular tachycardia or ventricular fibrillation in 6.2% of cases, pulseless electrical activity in 21.0%, asystole in 38.3% and was unknown or undocumented in the remaining 34.5%. Multivariate logistic regression analysis demonstrated increased 30-day survival with younger age, shockable cardiac rhythms, and daytime arrest. 30-day survival was 8.1% for EMS-assessed patients and 8.6% for EMS-transported patients. Conclusions: Philadelphia's reported incidence is consistent with urban settings although the survival rate is higher than other urban centers.